Manufacture and Characterization of Sensor for Optimizing the Manufacture of Resistance Sensor for Pure Orange Drink and Unpure Orange Drink - Widyaningrum, Siti Annisa; Ismawati, Ratri; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2020)
This research was purposed to design and analyze a resistance sensor. This research was done by three steps which are designing, manufacturing and characterizing of resistance sensor. Sensor design was done by using Fritzing software. The tools we used in manufacturing sensor were PCB, resistor, and copper wire. The tools we used in sensor characterizing were power supply, CRO and samples of pure orange drink and unpure orange drink. Sensor characterizing was done by varying samples of 50 ml and 100 ml. Data acquisitiom for each samples were repeated five times. Data generated from the sensor in the form of voltage. The data result of measurement were calculated by its average and its uncertainty. For pure orange drink 50 mL (2.274 ± 1.137); 100 mL (1.688 ± 0.844) and for unpure orange drink 50 mL (2.582 ± 1.291); 100 mL (1.852 ± 0.926). Therefore in the future we can make quality control system of orange drink by optimizing the manufacture of resistance sensors with high-grade characteristics.